Strategi Pengembangan Ekonomi Syariah di Kota Medan Menggunakan Analisis SWOT - Fauziah Nur Hutauruk (Journal of Islamic Economics and Finance, 2023)
The development of an Islamic-based economy in Indonesia has spread to many fields, both financial and non-financial. It is very clear that the Islamic financial system in Indonesia has the ability to encourage faster economic growth and increase financial stability with the aim of improving the welfare of individuals and society. Strategic steps are needed to optimize the sharia economic system at the national and international levels so that the effect is greater. The purpose of this paper is to philosophically analyze the structure of the sharia economy, as well as the methods and systems needed to accelerate sharia economic growth in the city of Medan. Strengths, weaknesses, opportunities and threats (SWOT) data analysis is used in this research to determine strategies for building an Islamic economic and business system in Medan City.